Systematic development of a mobile preconception lifestyle programme for couples undergoing IVF: the PreLiFe-programme. Issue 9 (11th August 2021) - Boedt, T; Matthys, C; Lie Fong, S; De Neubourg, D; Vereeck, S; Seghers, J; Van der Gucht, K; Weyn, B; Geerts, D; Spiessens, C; Dancet, E A F
Abstract: STUDY QUESTION: Can we develop a preconception lifestyle programme for couples undergoing IVF that is in line with their needs. SUMMARY ANSWER: A mobile preconception lifestyle programme was systematically developed based on expert opinion, literature and needs of IVF-patients. WHAT IS KNOWN ALREADY: A healthy lifestyle prior to conception is not only beneficial for the general health of couples, but evidence on its importance for their reproductive health and the health of their children is also emerging. So far, the vast majority of fertility clinics do not offer a lifestyle programme for couples undergoing IVF. Therefore, the present study aimed to develop a lifestyle programme for IVF-couples. STUDY DESIGN, SIZE, DURATION: The development of the PreLiFe-programme was guided by the steps of the Medical Research Council (MRC) framework for developing complex interventions, a systematic approach for developing theory- and evidence-based health promotion interventions. PARTICIPANTS/MATERIALS, SETTINGS, METHODS: First, the evidence base on lifestyle programmes for IVF-couples was reviewed. Second, several iterations between an expert panel, the literature, and quantitative and qualitative data from IVF-patients identified the content, the format, behaviour change techniques and theory of the programme. Third, the PreLiFe-programme was produced and the expected process and outcomes of a randomized controlled trial assessing it were modelled. Finally, user tests among experts and patients and pilot tests among patients were conducted. MAIN RESULTS AND ROLE OF CHANCE: The finally developed PreLiFe-programme is a mobile application to be used autonomously by both partners of IVF-couples during the first year of IVF, in combination with motivational interviewing over the telephone every three months (i.e. blended care). The PreLiFe-programme provides advice and skills training on physical activity, diet and mindfulness based stress reduction and is in part tailored based on monitoring and tracking the lifestyle of patients. Based on the literature the expert panel considers it plausible that all three components contribute to IVF-success rates. The PreLiFe-programme is likely to be acceptable to patients as it meets the need of patients for lifestyle advice and treatment information. LIMITATIONS, REASON FOR CAUTION: The pilot in IVF-couples had a 3-month duration. The feasibility of the PreLiFe-programme in other infertile populations and/or upon longer use is yet to be examined. Whether the PreLiFe-programme effectively improves lifestyle and IVF-success rates is currently being examined in a trial randomizing heterosexual couples starting IVF to the PreLiFe-programme or an attention-control group for 12 months. WIDER IMPLICATIONS OF THE FINDINGS: If the PreLiFe-programme improves lifestyle and the chance of IVF-success, it will be a powerful tool and provide guidance for implementing lifestyle programmes in fertility clinics. STUDY FUNDING/COMPETING INTEREST(S): Funded by the Research Foundation Flanders (FWO-TBM (Applied Biomedical Research with a Primary Social finality); reference: T005417N). The authors have no conflict of interest to report. TRIAL REGISTRATION NUMBER: NCT03790449.